Mixed medullary—papillary thyroid carcinoma with mixed lymph node metastases: A case report - Guerreiro, Vanessa (Clin Case Rep, 2021)
Mixed medullary‐follicular‐derived carcinoma is a very rare event. It is extremely important to make the correct diagnosis, due to prognostic and treatment implications. A genetic study of these patients is advisable to exclude the presence of MEN 2.